1997
DOI: 10.1007/s004420050188
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ultraviolet radiation on early larval stages of the Alpine newt, Triturus alpestris , under natural and laboratory conditions

Abstract: Although Alpine newts (Triturus alpestris) are found at altitudes up to 2500 m, their larvae proved to be extremely sensitive to UV radiation when exposed in clear tapwater to natural sunlight or to comparable artificial UV-B radiation in the laboratory. The experiments revealed severe skin damages (lysis of epithelial cells) and mortality after a few days of exposure. In their natural habitats above the timberline, however, the larvae are protected by the high concentration of dissolved organic carbon in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
85
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(91 citation statements)
references
References 25 publications
6
85
0
Order By: Relevance
“…Briefly, field and laboratory studies have shown that exposure to UVR can reduce survival, reduce growth, slow the rate of development, induce developmental malformations and abnormalities, reduce locomotor performance, and cause changes in metabolic rate and behaviour (Table 1). Such lethal and sublethal UVR effects have been observed in the embryos, larvae, metamorphs and adults of Limnodynastes peronii Artificial lamps [147] Lithobates sylvaticus Artificial lamps [93] Litoria aurea Ambient sunlight [177] Pseudacris cadaverina Ambient sunlight [179] Rana aurora Ambient sunlight plus artificial lamps [96] Rana cascadae Ambient sunlight [100] Taricha torosa Ambient sunlight [179] Reduced larval survival Ambystoma laterale Ambient sunlight plus artificial lamps [181] Ambystoma macrodactylum Artificial lamps [78,182] Ambystoma maculatum Ambient sunlight plus artificial lamps [181] Anaxyrus americanus Ambient sunlight plus artificial lamps [181] Artificial lamps [93] Bufo bufo Ambient sunlight [180,183] Crinia signifera Ambient sunlight [114] Hyla versicolor Ambient sunlight plus artificial lamps [181] Artificial lamps [93] Hypsiboas pulchellus Artificial lamps [69] Ichthyosaura alpestris Ambient sunlight [81] Artificial lamps [81] Limnodynastes peronii Artificial lamps [62,65] Lithobates clamitans Ambient sunlight [184] Ambient sunlight plus artificial lamps [181] Artificial lamps [93] Lithobates pipiens Ambient sunlight [184][185][186] Artificial lamps [58] Lithobates septentrionalis Ambient sunlight [184] Lithobates sylvaticus Ambient sunlight [188] Ambient sunlight plus artificial lamps …”
Section: Effects Of Uvr On Amphibiansmentioning
confidence: 99%
See 2 more Smart Citations
“…Briefly, field and laboratory studies have shown that exposure to UVR can reduce survival, reduce growth, slow the rate of development, induce developmental malformations and abnormalities, reduce locomotor performance, and cause changes in metabolic rate and behaviour (Table 1). Such lethal and sublethal UVR effects have been observed in the embryos, larvae, metamorphs and adults of Limnodynastes peronii Artificial lamps [147] Lithobates sylvaticus Artificial lamps [93] Litoria aurea Ambient sunlight [177] Pseudacris cadaverina Ambient sunlight [179] Rana aurora Ambient sunlight plus artificial lamps [96] Rana cascadae Ambient sunlight [100] Taricha torosa Ambient sunlight [179] Reduced larval survival Ambystoma laterale Ambient sunlight plus artificial lamps [181] Ambystoma macrodactylum Artificial lamps [78,182] Ambystoma maculatum Ambient sunlight plus artificial lamps [181] Anaxyrus americanus Ambient sunlight plus artificial lamps [181] Artificial lamps [93] Bufo bufo Ambient sunlight [180,183] Crinia signifera Ambient sunlight [114] Hyla versicolor Ambient sunlight plus artificial lamps [181] Artificial lamps [93] Hypsiboas pulchellus Artificial lamps [69] Ichthyosaura alpestris Ambient sunlight [81] Artificial lamps [81] Limnodynastes peronii Artificial lamps [62,65] Lithobates clamitans Ambient sunlight [184] Ambient sunlight plus artificial lamps [181] Artificial lamps [93] Lithobates pipiens Ambient sunlight [184][185][186] Artificial lamps [58] Lithobates septentrionalis Ambient sunlight [184] Lithobates sylvaticus Ambient sunlight [188] Ambient sunlight plus artificial lamps …”
Section: Effects Of Uvr On Amphibiansmentioning
confidence: 99%
“…Reduced larval escape swimming speed Limnodynastes peronii Artificial lamps [65,168] Reduced metamorph jumping performance Hypsiboas pulchellus Artificial lamps [69] Metabolism Reduced whole-animal metabolic rate in larvae Bufo bufo Artificial lamps [197] Limnodynastes peronii Artificial lamps [37] Increased whole-animal metabolic rate in larvae Bufo bufo Artificial lamps [197] Increased tissue metabolic rate in larvae Limnodynastes peronii Artificial lamps [37] Behaviour Erratic swimming behaviour Ichthyosaura alpestris Ambient sunlight [81] Artificial lamps [81] Lithobates sylvaticus Artificial lamps [93] Swimming in circles Lithobates pipiens Artificial lamps [58] Lithobates sylvaticus Artificial lamps [93] Reduced activity levels Hyla versicolor Artificial lamps [90] Limnodynastes peronii Artificial lamps [37] Rana aurora Artificial lamps [88] Rana cascadae Artificial lamps [155] Xenopus laevis Artificial lamps [90] Reduced predator avoidance Anaxyrus boreas Artificial lamps [64] Changed microhabitat use Ambystoma barbouri Ambient sunlight [80] Ambystoma texanum Ambient sunlight [80] Oophaga pumilio Ambient sunlight [201] Ambient sunlight plus artificial lamps [201] ability. Alton et al [66], on the other hand, found no effect of increased UVR exposure on either tadpole morphology or escape swimming performance.…”
Section: Effects Of Uvr On Amphibiansmentioning
confidence: 99%
See 1 more Smart Citation
“…Avoidance of UV has been observed in bacteria (Bebout and Garcia-Pichel, 1995;Häder, 1987;Kruschel and Castenholz, 1998), protozoans (Barcelo and Calkins, 1979), nematodes (Edwards et al, 2008), echinoderms (Adams, 2001;Pennington and Emlet, 1986), amphibians (Han et al, 2007;Nagl and Hofer, 1997;van de Mortel and Buttemer, 1998), fish (Fukunishi et al, 2006;Holtby and Bothwell, 2008;Kelly and Bothwell, 2002), crustaceans (Barcelo and Calkins, 1979;Barcelo and Calkins, 1980;Storz and Paul, 1998), insects (Bothwell et al, 1994;Mazza et al, 1999;Mazza et al, 2002) and mites (Barcelo, 1981;Barcelo and Calkins, 1980;Onzo et al, 2010;Sakai and Osakabe, 2010;). In addition, mites are attracted to visible radiation (VIS) (Dimock and Davids, 1985;Hussey and Parr, 1963;McEnroe and Dronka, 1966;McEnroe and Dronka, 1969;Mori, 1962;Naegele et al, 1966;Suski and Naegele, 1963a;Suski and Naegele, 1963b).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, increasing UV-B exposure has been hypothesized as a cause of observed declines and malformations in populations of many amphibian taxa others 1994a, Kiesecker andBlaustein and others 1997;Nagl and Hofer 1997;Ankley and others 1998Ankley and others , 2000Ankley and others , 2002Hader and others 1998;Pounds 2001;Tietge and others 2001;1994b;Palen and others 2003). This is a particularly tenable hypothesis for several reasons, including the correspondence between the recent increase in UV-B flux and field observations of effects in amphibians, the global distribution of both phenomena, and the potential for relatively high UV exposure of many amphibians.…”
Section: Introductionmentioning
confidence: 99%